Hybrid neural network model for forecasting market behaviour - Belzetsky, Anatoly I. (Journal of the Belarusian State University. Economics, 2023)
For improving the quality of forecasting market behaviour, a hybrid model that combines models of organised market integrity and an artificial neural network is proposed. The hybrid model allows us to take into account the heterogeneous spatiotemporal structure of the market in interaction with the external environment, to take into account non-linear effects and to make a reliable forecast of the main market indicators for several future periods. An example of neural network forecasting of financial market behaviour, confirming the quality of the hybrid model is presented.
Keywords: market; hybrid model; neural network; forecasting; behaviour; organised integrity